Pathways to Progress: Unveiling Structural Change in Africa Through Economic Transformation, Technology, Talent, and Tourism - Hugo Pinto; Evans Odoi; Carla Nogueira; Luiz Fernando Câmara Viana (Economies)
African economies are undergoing significant structural transformation, transitioning from agriculture to manufacturing, services, and technology-driven industries. Driven by urbanization, technological innovation, and global trade, this shift offers opportunities for sustainable growth but faces challenges such as infrastructure gaps and institutional hurdles. This paper examines the dynamics of structural change in 54 African countries, focusing on the roles of technology, talent, and tourism. Using World Bank data, factor and cluster analyses reveal five latent components: structural conditions, public sector capacities, dynamic conditions, urbanization, and growth. The analysis categorizes countries into six clusters, from Developing Economies to African Powerhouses. The findings emphasize the critical role of technology in boosting productivity, the importance of talent development through education and workforce integration, and the potential of sustainable tourism to drive transformation. This research provides a comprehensive framework for understanding Africa’s structural transformation, offering actionable insights to address disparities and promote equitable development across the continent.